Erosion Mechanism Assessment and Scour Depth Prediction of Offshore Cemented Sand Using Erosion Function Apparatus - Park, Suhyuk; Park, Jinwoo; Chang, Ilhan (Geotechnical Special Publication, 2025)
Erosion is a common occurrence in coastal or riverbed areas, particularly where structures interface with the soil. In addition, turbulence around piles accelerates erosion significantly and poses a threat to pile stability by causing extreme erosion of the surrounding ground. This is called scour. Predicting the depth of scour that will occur around the pile is therefore a critical aspect of pile structure construction. This study focuses on evaluating the physical and mechanical properties of core-cemented sand seafloor deposits. To assess soil erosion, the state-of-the-art Erosion Function Apparatus (EFA) with P-wave monitoring method is used in this study. Main erosion parameters (i.e., critical shear stress and erodibility coefficient) were obtained from the EFA test and then the SRICOS-EFA program was employed to predict the possible scour behavior around the pier structure. The EFA test results showed significant differences in soil classifications, with L3 soil showing low resistance to shear stress and L4 soil demonstrating the highest resistance. Using SRICOS-EFA method, a scour depth of 1.56 m was predicted for both soft and hard soils over 25 years, with deeper scour occurring during high discharge events. Accurate hydrograph data is essential for precise scour predictions. Further EFA tests and in situ measurements at various depths are recommended for better scour assessment.
Keywords: Cemented sands; Depth of scours; Erosion function apparatus; Erosion mechanisms; Offshores; Physical and mechanical properties; Scour depth; Seafloors; Soil erosion; Structure constructions